Indicators of transport and vertical motion from correlations between in situ measurements in the Airborne Antarctic Ozone Experiment - Murphy, D. M.; Tuck, A. F.; Kelly, K. K.; Chan, K. R.; Loewenstein, M.; Podolske, J. R.; Strahan, S. E. (1989)
Analysis of small-scale structure in the in situ measurements made from the ER-2 during the Airborne Antarctic Ozone Experiment shows the existence of a region at the boundary of the chemiclly perturbed region where the mixing ratios and small-scale structure of trace gases are influenced by transport across the boundary. This transition region is characterized by horizontal interchange and vertical layering of air parcels from within and outside of the chemically perturbed region and negative small-scale correlations between ClO and ozone. The horizontal transport in this region creates large surface areas between dissimilar air masses, providing the potential for substantial mixing. Correlations between ClO and O3 show that the transition region extends to 2-4 deg of latitude to either side of the boundary of the chemically perturbed region. A + or - 4-deg-wide transition region would contain nearly as much air as the chemically perturbed region proper. Analysis of water vapor and nitrous oxide data suggests that diabatic descent is associated with dehydration. This could be caused by strong radiative cooling of those polar stratospheric clouds in which enough water condenses for the particles to fall and dehydrate the air.